Geo-Chicago 2016 : sustainable waste management and remediation : selected papers from sessions of Geo-Chicago 2016, August 14-18, 2016, Chicago, Illinois - Yesiller, Nazli; Zekkos, Dimitrios; Farid, Arvin; De, Anirban; Reddy, Krishna R. (American Society of Civil Engineers, 2016)
Contains 75 peer-reviewed papers on remediation, containment, public policy, and education in geoenvironmental engineering. Topics include: sustainable waste management and remediation; containment rate and transport; electrokinetic remediation; contaminated sediments; remediation methods; solidificaton/stabilization; and public policy and regulations.
Sponsored by Geo-Institute of the American Society of Civil Engineers.
Keywords: Environmental geotechnology -- Congresses.; Refuse and refuse disposal -- Congresses.; Soil pollution -- Congresses.; Soils -- Heavy metal content -- Congresses.; Sediment transport -- Congresses.; Soil remediation -- Congresses.; Hazardous waste site remediation -- Congresses.; elektronické knihy; electronic books